The fear of coronavirus scale: exploratory and confirmatory factor analysis - Wibowo, Yoga Setyo; Utami, Rizki Karya; Nadia, Yunita; Nizeyumukiza, Emmanuel; Setiawati, Farida Agus (Konselor, 2020)
Although the problem of anxiety and fear has not been a priority in the treatment of coronavirus, the results of studies show that there is an increase in people's fear of coronavirus. This study aims to evaluate and confirm the Fear of COVID-19 Scale (FCV-19S) Â in the Indonesian population. Exploratory Factor Analysis and Confirmation Factor analysis were used for this purpose. A total of 117 participants responded to the scale. The results of the EFA showed that the scale has two dimensions. Furthermore, the results of the CFA revealed that the Indonesian version of FCV-19S exhibited very good construct validity (factorial and convergent), and acceptable reliability. These findings suggest that the Indonesian version of FCV-19S is a developmentally appropriate instrument that can be used to examine fears of coronavirus in Indonesia.